2007
DOI: 10.1128/mcb.00323-07
|View full text |Cite
|
Sign up to set email alerts
|

Ligand-Independent Regulation of Transforming Growth Factor β1 Expression and Cell Cycle Progression by the Aryl Hydrocarbon Receptor

Abstract: The aryl hydrocarbon receptor (AHR) is a ligand-activated transcription factor that mediates the toxic effects of its xenobiotic ligands and acts as an environmental checkpoint during the cell cycle. We expressed stably integrated, Tet-Off-regulated AHR variants in fibroblasts from AHR-null mice to further investigate the AHR role in cell cycle regulation. Ahr ؉/؉ fibroblasts proliferated significantly faster than Ahr ؊/؊ fibroblasts did, and exposure to a prototypical AHR ligand or deletion of the ligand-bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
97
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 95 publications
(101 citation statements)
references
References 74 publications
4
97
0
Order By: Relevance
“…In non-malignant cells of AhR null mice, the LTBP-1/TGF-b pathway by AhR is regulated by diverse mechanisms. These include post-translational regulatory mechanisms, as described for primary hepatocytes (Zaher et al, 1998), regulation of mRNA levels (Chang et al, 2007) and cytokine activation in the extracellular matrix of embryonic fibroblasts (Gomez-Duran et al, 2006). The fact that LTBP-1 may activate TGF-b in the absence of altering total TGF-b levels in LN-308 cells (Tritschler et al, 2009) adds complexity to this issue.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In non-malignant cells of AhR null mice, the LTBP-1/TGF-b pathway by AhR is regulated by diverse mechanisms. These include post-translational regulatory mechanisms, as described for primary hepatocytes (Zaher et al, 1998), regulation of mRNA levels (Chang et al, 2007) and cytokine activation in the extracellular matrix of embryonic fibroblasts (Gomez-Duran et al, 2006). The fact that LTBP-1 may activate TGF-b in the absence of altering total TGF-b levels in LN-308 cells (Tritschler et al, 2009) adds complexity to this issue.…”
Section: Discussionmentioning
confidence: 99%
“…The wide range of toxic effects induced by these compounds, including birth defects, impaired reproductive capacity and altered immune responses, have encouraged research on the interaction of AhR with sex steroid receptors and the immune system (Ohtake et al, 2008;Quintana et al, 2008;Veldhoen et al, 2008). AhR regulates cellular differentiation during development (Huang et al, 2004;Lahvis et al, 2000) and may promote cell cycle progression in the absence of exogenous ligand (Chang et al, 2007;Marlowe and Puga, 2005). There is also an emerging evidence for a prominent role of AhR in tumorigenesis.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to its role in the regulation of drug metabolism, evidence dating back more than 20 years shows that the AHR plays a central role in the regulation of cell proliferation. AHR activation by ligand or by deletion of the ligandbinding domain alters several cell cycle and signaling pathways, including those required for normal cell cycle regulation (Puga et al, 2002;Chang et al, 2007). Most evidence shows that AHR activation delays cell cycle progression and G 1 to S phase transition, although this effect seems to be cellular context specific, because in rat oval progenitor cells the AHR promotes rather than delays cell cycle progression (Weiss et al, 2008).…”
mentioning
confidence: 99%
“…Most evidence shows that AHR activation delays cell cycle progression and G 1 to S phase transition, although this effect seems to be cellular context specific, because in rat oval progenitor cells the AHR promotes rather than delays cell cycle progression (Weiss et al, 2008). A canonical RB-binding cyclin D-like motif in the AHR protein sequence mediates a direct interaction between AHR and RB, and experimental work focused on the characterization of this interaction as the mediator of AHR-dependent cell cycle delay (Ge and Elferink, 1998;Puga et al, 2000;Marlowe et al, 2004;Huang and Elferink, 2005) has shown that the activated AHR cooperates with RB in its ability to repress E2F-dependent transcription and delay cell cycle progression Strobeck et al, 2000).Paradoxically, embryo fibroblasts from Ahr gene-knockout mice also show a relative delay in cell cycle progression, which has been primarily associated with posttranscriptional stabilization of Tgfb1 mRNA (Chang et al, 2007). In these cells, several E2F transcriptional targets with AHR and E2F binding motifs in their promoters, conserved in both the human and mouse sequences (Supplemental Tables S1 and S2), were also found to be AHR targets, being repressed by both E2f1 and Ahr ablation (Supplemental Figure S1).…”
mentioning
confidence: 99%